Adsorption solar air conditioning system for Singapore climate - Tamainot-Telto, Zacharie (2022)
The design of an adsorption solar air conditioning system is investigated by using a model with an activated carbon–methanol working pair. This system is analysed with the solar insolation levels and ambient temperatures of Singapore. The proposed design mainly consists of two tubular reactor heat exchangers (TRHEXs) operating out of phase and driven by heat from an evacuated tube solar collector (ETSC). The pair of TRHEXs act as a thermal compressor and contain about 2.275 kg of activated carbon per reactor. The evacuated tube solar collector (ETSC) has better performance and is more cost effective than the flat plate solar collector (FPSC), even though it has a higher cost per unit. On the hottest day of the year, the proposed adsorption system has a maximum cooling power of 2.6 kW and a COP of 0.43 at a maximum driving temperature of 139 °C with a 9.8 m2 ETSC area. The system has a total estimated cost of EUR 10,550 corresponding to about SGD 14,800 with a 7-year payback time. At similar cooling capacities, the adsorption air conditioning system is expected to be more cost effective than the conventional system beyond an expected period of 7 years, with an expected lifetime of 15 to 20 years.